Highly Rated and most Frequent Stressors among Police Officers: Gender Differences - Violanti, John M. (American journal of criminal justice, 2016)
This descriptive study examined the top five most frequent and highly rated occupational stressors from the Spielberger Police Stress Survey among 365 police officers enrolled in the Buffalo Cardio-Metabolic Occupational Police Stress (BCOPS) Study (2004–2009). Prevalence, frequency, and rating of stressors were compared across gender. Poisson regression was used to estimate the prevalence and prevalence ratio (PR) of events. Analysis of variance was used to compare mean frequency of occurrence and mean stress ratings by gender. Many reported stressors dealt with violent situations. Responding to family disputes (83 %) was reported as the most frequent stressor and exposure to battered children (27 %) was the most highly rated stressor (mean rating: 67.6 ± 35.3). Killing someone in the line of duty (mean rating: 66.3 ± 43.0) and experiencing a fellow officer being killed (mean rating: 65.3 ± 40.6) were highly rated but infrequent (0.27 % and 3.6 %, respectively). Male officers tended to report more frequent stressors which took away from their time off duty such as court appearances (PR = 1.26, 1.04–1.52) and working second jobs (PR = 2.37, 1.57–3.57). In contrast, female officers reported experiencing a 37 % higher prevalence of lack of support from supervisor (PR = 0.63, 0.48–0.82) relative to male officers. Results of the present study are discussed within the context of specific police stressors and gender.